Results-based leadership - Ulrich, David 1953-; Zenger, John H.; Smallwood, W. Norm (Harvard Business School Press, 1999)
"Results-Based Leadership challenges the conventional wisdom surrounding leadership. The authors - experts in human resources and leadership development - argue that it is not enough to gauge leaders by personal traits such as character, knowledge, style, and values. Effective leaders, say the authors, do more than master the attributes of leadership. They know how to connect their attributes with results." "Results-Based Leadership shows executives how to deliver results in four specific areas: results for employees, the organization, its customers, and its investors. The authors provide action-oriented guidelines for readers to develop and hone their own results-based leadership skills. They look beyond the quick fixes, buzzwords, and trends that typify many leadership programs, and focus instead on producing results that can be measured and integrated into any business strategy or corporate culture."--BOOK JACKET.